Design of dental implants, influence on the osteogenesis and fixation - Vasconcellos, Luana M. R. [UNESP]; Oliveira, Marize V.; Graca, Mario L. A.; Vasconcellos, Luis G. O. [UNESP]; Cairo, Carlos A. A.; Carvalho, Yasmin R. (Springer, 2008)
The fixation and the bone ingrowth at the interface of porous cylindrical implants (total porosity of 37% and average pores diameter of 480 mu m) were compared in vivo to rough cylindrical implants (R-a = 5.3 mu m), both of commercially pure titanium, made by powder metallurgy. The implants were inserted into the tibias of 20 rabbits and the animals were sacrificed 4 and 8 weeks after surgery. The percentage of bone-implant contact observed in porous implant was significantly larger than in the rough ones for all of sacrifice periods, respectively, 57% vs. 46% after 4 weeks, and 59% vs. 50% after 8 weeks. The mechanical tests showed a significant increase in the shear strength of the porous implants for the two analyzed periods, 4 and 8 weeks (14 and 20 MPa), when compared with rough ones (4 and 13 MPa). These results suggest that porous implants improve the contact at the implant-bone interface and increase the fixation to the bone, improving the osseointegration. Thus, the porous implant might be an alternative to dental implant in less favorable conditions, and appear to be better fixed to bone, offering promising alternatives.